2019
DOI: 10.1155/2019/7420781
|View full text |Cite
|
Sign up to set email alerts
|

VR Locomotion in the New Era of Virtual Reality: An Empirical Comparison of Prevalent Techniques

Abstract: The latest technical and interaction advancements within the virtual reality (VR) field have marked a new era, not only for VR, but also for VR locomotion. In this era, well-established, prevalent VR locomotion techniques are mostly used as points of comparison for benchmarking of new VR locomotion designs. At the same time, there is the need for more exploratory, comparative studies of contemporary VR locomotion techniques, so that their distinguished interaction aspects can be documented and guide the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…In some studies, special data may be sought that rely on unique hardware. To compare devices and select the optimal one, further advice can be found through available studies [ 46 , 57 , 58 ], consultation with colleagues, manufacturer specifications, and technical support. The type of both internal and external sensors that are employed should also be carefully considered.…”
Section: Methodological Guidelines For Ive Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, special data may be sought that rely on unique hardware. To compare devices and select the optimal one, further advice can be found through available studies [ 46 , 57 , 58 ], consultation with colleagues, manufacturer specifications, and technical support. The type of both internal and external sensors that are employed should also be carefully considered.…”
Section: Methodological Guidelines For Ive Study Designmentioning
confidence: 99%
“…Until now, only a handful of studies have tested the quality of walking experience using IVEs. Using quantitative questionnaires and semi-structured interviews, Boletsis and Cedergren [ 57 ] compared user experiences of three common locomotion IVE techniques: (1) walking-in-place (without an omnidirectional treadmill); (2) controller/joystick-driven movement, where participants use a hand controller or joystick to direct their movement; and (3) teleportation, in which users advance from one teleportation point to another by pointing with the hand controller to the next point (i.e., advancement in the IVE is made through non-continuous jumps). The researchers concluded that the walking-in-place technique generated a greater sense of immersiveness due to the naturalness of the walking, as well as enjoyment.…”
Section: Using Virtual Reality To Study Human Behavior and Mobilitmentioning
confidence: 99%
“…In addition, he emphasizes that the use of immersive VR-based technology can enrich us with additional extremely real experiences that are not experienced during a visit to a real physical area and can appear as a kind of design support option in the field of landscape architecture and research. C. Boletsis et al [37] present and analyze the user experiences provided by contemporary and now widespread VR movement techniques through empirical research. The results of the study show that users delve into virtual space mostly through a walking-in place, but this also means the greatest psychophysical strain on them.…”
Section: Virtual Reality (Vr)mentioning
confidence: 99%
“…(T1) Put on the HMD -look around and listen (T2) Walking navigation (T3) Navigation by teleportation [4] (T4) Walking to and investigating a gravestone (T5) Walking to and investigating the monument (T6) Placing a candle (T7) Visualisation of the number of fallen soldiers, Fig. 4 After completing the tasks, participants completed an end questionnaire which also asked for feedback on 6 additional concept ideas for the virtual graveyard: (C1) A link from the gravestone to a map showing the location where the body originally lay (C2) Showing the virtual graveyard at different times of the day or seasons of the year (C3) Placing a wreath or flowers on a grave (C4) Planting a small tree in the graveyard and watching it grow remotely from home (C5) Detailed information on individual soldiers linked to their grave e.g.…”
Section: Study Proceduresmentioning
confidence: 99%